Choosing a travel agency franchise by mean of a global composite indicator: an application in Spain - Blancas-Peral, Francisco J.; Contreras, Ignacio; Ramírez-Hurtado, José M. (Journal of Business Economics and Management, 2014)
This paper highlights the complexity of the franchise partner selection process from a franchisee's perspective. The purpose of this article is, firstly, to propose the definition of a system of indicators which include all the relevant information which the potential franchisee should take into consideration when choosing a chain secondly, to obtain a global composite indicator for the construction of a ranking of franchisors. In order to illustrate the procedure, a sample of travel agency franchisors in Spain and a suitable database to quantify the indicators are considered. The paper concludes constructing a complete order of the franchisors in the travel agency industry. In addition, the results show the most important characteristics of franchisors that potential franchisees must take into account. The value of the paper is significant as it provides a practical frame – work for potential franchisees in the selection of franchisors.First published online: 12 Sep 2012